Changes in Digestive Microbiota, Rumen Fermentations and Oxidative Stress around Parturition Are Alleviated by Live Yeast Feed Supplementation to Gestating Ewes - Lysiane Dunière; Damien Esparteiro; Yacine Lebbaoui; Philippe Ruiz; Mickael Bernard; Agnès Thomas; Denys Durand; Evelyne Forano; Frédérique Chaucheyras-Durand (Journal of Fungi, 2021)
Background: In ruminants, physiological and nutritional changes occur peripartum. We investigated if gastro-intestinal microbiota, rumen metabolism and antioxidant status were affected around parturition and what could be the impact of a daily supplementation of a live yeast additive in late gestating ewes. Methods: Rumen, feces and blood samples were collected from 2 groups of 14 ewes one month and a few days before parturition, and 2 weeks postpartum. Results: In the control ewes close to parturition, slight changes in the ruminal microbiota were observed, with a decrease in the concentration F. succinogenes and in the relative abundance of the Fibrobacteres phylum. Moreover, a decrease in the alpha-diversity of the bacterial community and a reduced relative abundance of the Fibrobacteres phylum were observed in their feces. Control ewes were prone to oxidative stress, as shown by an increase in malondialdehyde (MDA) concentration, a lower total antioxidant status, and higher glutathione peroxidase (GPx) activity in the blood. In the yeast supplemented ewes, most of the microbial changes observed in the control group were alleviated. An increase in GPx activity, and a significant decrease in MDA concentration were measured. Conclusions: The live yeast used in this study could stabilize gastro-intestinal microbiota and reduce oxidative stress close to parturition.